PRINCIPLES OF FORMATION OF EDUCATIONAL AND RESEARCH ACTIVITIES IN PHYSICAL EDUCATION (Scientific journal of the Fergana State University, 2024)
The article discusses the importance of educational and research activities in the formation of physical knowledge, the stages of formation of educational and research activities in physical education.The principles of educational and research activities and methods of organization as individuals and the successful achievement of educational goals in the educational process are scientifically substantiated. The role of educational and research activities in the development of the scientific worldview of students, the issues of their formation in a logical sequence, in accordance with the purpose, is described. A methodological model of the organization is recommended to improve the educational and research activities of students in physical education.